Modifications of SME Biomass Boiler for High Efficiency Multi-Fuel Input - Krittipat Piawanich (2019)
© 2018 Asian Institute of Technology. This research focuses on modifications of a conventional biomass burner for a vertical fire-tube boiler to accept multiple fuel with increased efficiency. The selected boiler for this work has thermal power output of 90 kWth using firewood as primary fuel. The main objective is to design and develop multi-fuel feeding system to accept other available biomass applicable to existing burner with minimal modifications of the main structure. After the burner was refitted with the feeding system, the optimum surplus combustion air was studied for three types of solid fuels; corn cob, wood chips and biomass pellets. A breakpoint analysis was conducted for each biomass fuel. It was found that before burner modification, the highest values of thermal efficiency of fire wood burner were 40.52%. After the change of burner feeding in accordance with air input improvements, the thermal efficiency of the burner for corn cob, wood chip and pellets were 54.18 %, 50.46 % and 69.41 % respectively. The semiautomatic fuel feed can be readily utilized for all three fuel types and feed rate could be reduced by 58.1.1%, 58.2% and 70.63% by weight respectively compared with firewood. It is also found that biomass pellets are the most suitable alternative fuel for roasting of parchment coffee with the lowest processing cost in comparison with other biomasses.